Suppressing migration of oxygen vacancies in acceptor-doped barium titanate - Xu, Zhanpeng (2025)
Barium titanate (BaTiO3) is an important ferroelectric material widely used to make multilayer ceramic capacitors (MLCCs) for various modern electronic devices primarily due to its extremely large relative permittivity. BaTiO3 adopts the perovskite structure (general formula: ABO3), and both the Ba-site and the Ti-site can be doped with different elements to tune dielectric and electrical properties. In the production process of MLCCs, to prevent the base metal electrodes such as copper (Cu) and nickel (Ni) from being oxidised, the BaTiO3 ceramic layers and the base metal electrodes are sintered together in a reducing atmosphere. However, the reducing atmosphere leads to oxygen loss in BaTiO3, resulting in the generation of electrons and undesired n-type semiconductivity. To minimise the generation of n-type semiconductivity in BaTiO3 during sintering at high temperatures and in a reducing atmosphere, low levels of acceptor doping such as doping Mg2+ at the Ti4+ site is needed. However, acceptor doping generates oxygen vacancies and can bring new challenges. The mobility of oxygen vacancies is typically very low around room temperature and under low electric fields. The presence of oxygen vacancies does not pose serious issues for low temperature, low electric field applications (e.g. mobile phones and computers). However, oxygen vacancies could become mobile at relatively high temperatures and under high electric fields, leading to fatal device failures due to rapid degradation of insulation resistance. This becomes an urgent and significant challenge for developing highly reliable MLCCs for high-voltage and high-temperature power electronics applications.